Measurement of the 242Pu(n,f) cross-section at the CERN n_TOF facility - Tsinganis, A.; Berthoumieux, E; Guerrero, C.; Colonna, N.; Calviani, M.; Vlastou, R.; Andriamonje, S.; Vlachoudis, V.; Gunsing, F.; Massimi, C.; n_TOF Collaboration, the (HNPS Advances in Nuclear Physics, 2019)
Knowledge of neutron cross-sections of various plutonium isotopes and other minor actinides is crucial for the design of advanced nuclear systems. The 240,242Pu(n,f) cross-sections were measured at the CERN n_TOF facility, taking advantage of the wide energy range (from thermal to GeV) and the high instantaneous flux of the neutron beam. In this work, preliminary results are presented along with a theoretical cross-section calculation performed with the EMPIRE code.